2018
DOI: 10.1109/tvt.2018.2876592
|View full text |Cite
|
Sign up to set email alerts
|

Power Minimization in Distributed Antenna Systems Using Non-Orthogonal Multiple Access and Mutual Successive Interference Cancellation

Abstract: This paper introduces new approaches for combining non-orthogonal multiple access with distributed antenna systems. The study targets a minimization of the total transmit power in each cell, under user rate and power multiplexing constraints. Several new suboptimal power allocation techniques are proposed. They are shown to yield very close performance to an optimal power allocation scheme. Also, a new approach based on mutual successive interference cancellation of paired users is proposed. Different techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 23 publications
0
50
0
Order By: Relevance
“…To the best of our knowledge, the problem of downlink power minimization in DAS networks with RRH power limits using NOMA has not been addressed yet. This problem is substantially different from the one in [14] since heavily loaded antennas are generally the most important players in minimizing the system power. Thus, setting power limits on some of them will necessarily raise the system power consumption.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…To the best of our knowledge, the problem of downlink power minimization in DAS networks with RRH power limits using NOMA has not been addressed yet. This problem is substantially different from the one in [14] since heavily loaded antennas are generally the most important players in minimizing the system power. Thus, setting power limits on some of them will necessarily raise the system power consumption.…”
Section: Introductionmentioning
confidence: 94%
“…In our previous work [14], we showed that two users k 1 and k 2 power-multiplexed on a subcarrier n and transmitted by two different RRHs r 1 (n) and r 2 (n) respectively, can perform mutual SIC, i.e. perform SIC simultaneously, if their channel gains verify:…”
Section: System Description and Problem Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…By a judicious power multiplexing, NOMA greatly outstrips the performance of its predecessor OMA (Orthogonal Multiple Access), widely used in 4G systems. It has also proved to be an important ally of multi-antenna transceivers in leveraging both energy and spectral efficiency of wireless systems, either in collocated [2] [3] or distributed antenna configurations [4]. Power-domain NOMA allows multiplexing two or several users on the same frequency subband by taking advantage of their channel gain difference [5].…”
Section: Introductionmentioning
confidence: 99%
“…PA is performed by maximizing EE under the constraints of total transmit power per RRH, target Bit Error Rate and proportional fairness among users. The problem of power minimization in DAS was considered in [4] with a joint allocation of subcarrier, RRH and power to users, so as to guarantee user target rates. However, none of these studies have accounted for the presence of a jammer in the system.…”
Section: Introductionmentioning
confidence: 99%